Systematic optimization of the Ni-to-Mo ratio in bimetallic Ni–Mo₂C catalysts for efficient selective hydrogenation of levulinic acid to γ-valerolactone - Ravichanon Sakdee; Sakhon Ratchahat; Chularat Sakdaronnarong; Wanida Koo-amornpattana; Wanwisa Limphirat; Sompin Mahakot; Suttichai Assabumrungrat; Atthapon Srifa (Fuel Processing Technology)
In this investigation, the optimization of Ni-to-Mo ratios in synergistic bimetallic Ni–Mo₂C catalysts was systematically investigated through a co-impregnation method, followed by the transformation of the calcined precursors into carbide structures via a carbothermal reduction process. The catalytic performance was evaluated for the hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL). Comprehensive physical and structural characterizations were carried out to elucidate the structure–activity relationships. In the designed NixMoyC catalysts, a Ni to Mo ratio of 1.0: 1.0, corresponding to the Ni1.0Mo1.0C catalyst, exhibited the highest activity for hydrogenating LA into GVL. The superior performance of the Ni1.0Mo1.0C catalyst is attributed to the synergistic interfacial electronic interactions between the metallic Ni0 and Mo2C species, along with the presence of well-ordered carbon layer structures. Under optimized reaction conditions (160 °C, 20 bar H₂ pressure, 8 h reaction time, and 20 wt% catalyst loading), the Ni1.0Mo1.0C catalyst achieved complete LA conversion and a GVL yield of 97.4 %. This high performance is attributed to its small particle size, improved H2 adsorption–desorption capacity, and the presence of appropriately distributed acidic sites. These findings highlight the competitive performance of Ni–Mo₂C catalysts for the efficient production of GVL from LA, offering promising applications in sustainable biorefinery processes.